Archival traditions in Latin America (2022)
ABSTRACT: This paper surveys archival traditions coexisting in Latin America and identifies key moments in the region's development of archives and archival practices. First, different record-keeping practices in pre-Hispanic communities are identified. Second, an Iberian conception of the archive is described in the case of colonial archival practices between the sixteenth and nineteenth centuries. Third, changes resulting from independence movements and the subsequent arrival of the Latin archival tradition are documented. Fourth, the emergence of an Ibero-American archival tradition is posited, which is State-sponsored and institutional and the product of a postwar context. Lastly, the turns and shifts these traditions are experiencing due to social conflict and transformations taking place in the region since the late twentieth century are presented, associated with marginal practices and with close attention being paid to users.